Bijak Menggunakan Media Sosial pada Masyarakat Digital - Handayani, Triana Dianita (AKADEMIK: Jurnal Mahasiswa Humanis, 2024)
Technological advancements have ushered in socio-cultural transformations, altering behavioral patterns and social and cultural elements within society and influencing the evolution of social systems and structures. Various factors, including the proliferation of digital technologies, drive these changes. The sophistication of digital technologies in today's social media landscape has facilitated the rapid and widespread dissemination of information to the public. However, this ease of access has also triggered behavioral shifts among digital users, leading to irresponsible social media usage. Misinformation (hoaxes) and cyberbullying have become prevalent, tarnishing Indonesia's reputation as a Southeast Asian nation with a notoriously impolite online community. In this digital era, digital citizens must cultivate greater discernment and responsibility in social media interactions, harnessing its potential as a platform for sharing information, insights, and knowledge. This shift is crucial to prevent society from becoming ensnared by the very technology it has created.